The factor model of personality perfectionism - Kononenko, Oksana I. (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
The multidimensionality of the structure is considered as the main criterion for the creation of the concept of diversified personality perfectionism. The perfectionism is seen as a global phenomenon, because exposure to it can cover all the spheres of life of the individual. And the pursuit to high standards is not itself pathological, but success brings the perfectionist pleasure, increases self-esteem, or maintains it at the proper level. It was presented a model of perfectionism and substantiated links of the cognitive, personal and behavioral factors, as well as built a model of personality that differs in the tendency to positive or negative perfectionism.